Precios relativos y exportaciones manufactureras españolas: ¿explotan las empresas industriales una cadena de valor multinacional? - Aláez, Ricardo; Fernández, Ana; García, Begoña (Estudios de Economía, 2016)
This paper analyses the Spanish manufacturing exports to the European Union. A panel data approach is used to test the hypothesis that there are differences among manufacturing branches exports in relation to their elasticity to short term variations in the real effective exchange rate index of the peseta. The main result is that exports of manufacturing branches controlled by local firms are more sensible to relative prices changes, but these branches have reduced their share on overall exports in the under consideration period. Furthermore, those manufacturing branches controlled by foreign-owned firms have revealed themselves less sensible to conjunctural variations in the real effective exchange rate index of the peseta, but have augmented their share in overall export value.